Criminalization and Decriminalization Policies in the New Concept of the Criminal Code - Hidayani, Sri; Mina, Revi Fauzi Putra (Universitas Islam Negeri Sumatera Utara, 2021)
Criminalization is related to policies that aim to create security and order within a country to regulate each layer of multicultural society. The criminalization policy only regulates actions that can cause damage and cause victims. So the policy exists to prohibit an act where the act was previously not prohibited (not against the law), this is related to the Principle of Legality, which is the principle which is the basis in the Criminal Code and a guide for the community so that policy makers (the government) do not arbitrarily in criminalizing society, because an act is prohibited and a sanction applies because there is a legal basis (criminalization policy). Then, in the Criminal Code there are policy matters related to the Decriminalization policy. Decriminalization is a policy where initially an act is prohibited and then changed to an act that is considered normal. In the Criminalization Policy there are various classifications of offenses which are of course in accordance with the new Criminal Code. One of them is the latest definition of